Genome-Wide Identification, Characterization of the ORA (Olfactory Receptor Class A) Gene Family, and Potential Roles in Bile Acid and Pheromone Recognition in Mandarin Fish (Siniperca chuatsi) - Xiaoru Dong; Maolin Lv; Ming Zeng; Xiaochuan Chen; Jiale Wang; Xu-Fang Liang (Cells)
The ORA (olfactory receptor class A) gene family in teleosts is related to the V1R (vomeronasal 1 receptors) family in mammals and plays a key role in odor detection. Although ORA genes have been identified in several teleosts, their characteristics in mandarin fish (Siniperca chuatsi) have not been explored. In this study, we conducted a comprehensive genomic analysis of the mandarin fish and discovered a complete ORA gene family consisting of five members located on chromosome 2 (ORA1, ORA2, ORA3, ORA4) and chromosome 16 (ORA6). Phylogenetic, synteny, and gene structure analyses revealed typical exon–intron conservation with strong evidence of purifying selection. Tissue expression analysis showed distinct expression profiles for each ORA gene, with some showing sexual dimorphism in specific tissues. The expression of ORA1 and ORA2 in the olfactory epithelium exhibits sexual dimorphism, while ORA3 shows sexual dimorphism in the brain. In situ hybridization confirmed that ORA1, ORA2, ORA3, and ORA6 are expressed in the microvillar sensory neurons of the olfactory epithelium, while ORA4 is expressed in crypt cells. Additionally, molecular docking simulations indicated that the five ORA proteins have a high binding affinity with seven bile acids (LAC, GLAC, CA, TLCA, 3-KLCA, 7-KLCA, and 12-KLCA), with ORAs showing stronger binding affinity with LCA and CA. This study comprehensively characterizes the ORA gene family in mandarin fish, examining its phylogeny, synteny, gene structure, and selection pressure. Furthermore, we found that each ORA displays a distinct expression pattern across multiple tissues, with notable sexual dimorphism, and shows potential binding interactions with specific bile acids and pheromones. Our findings provide valuable insights that enhance the overall understanding of fish ORAs and their potential functions.